2001
DOI: 10.1074/jbc.m009808200
|View full text |Cite
|
Sign up to set email alerts
|

Vitreoscilla Hemoglobin

Abstract: The obligate aerobic bacterium, Vitreoscilla, synthesizes elevated quantities of a homodimeric hemoglobin (VHb) under hypoxic growth conditions. Expression of VHb in heterologous hosts often enhances growth and product formation. A role in facilitating oxygen transfer to the respiratory membranes is one explanation of its cellular function. Immunogold labeling of VHb in both Vitreoscilla and recombinant Escherichia coli bearing the VHb gene clearly indicated that VHb has a cytoplasmic (not periplasmic) localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(30 citation statements)
references
References 40 publications
1
28
1
Order By: Relevance
“…These questions might be answered using site-directed mutants; a nonoxygen binding mutant of VHb could be used to test the former, for example, and exterior surface mutants the latter. In the previously reported binding studies (13), VHb bound equally well to both E. coli and Vitreoscilla membranes, which is supported by the results of the two-hybrid assay of the current study. An interaction between cytochrome bo and VHb was suggested by Tsai et al (3).…”
Section: Construction Of Peg202::vgb and Pjg4-5::cyo Bo Ubiquinolsupporting
confidence: 75%
See 2 more Smart Citations
“…These questions might be answered using site-directed mutants; a nonoxygen binding mutant of VHb could be used to test the former, for example, and exterior surface mutants the latter. In the previously reported binding studies (13), VHb bound equally well to both E. coli and Vitreoscilla membranes, which is supported by the results of the two-hybrid assay of the current study. An interaction between cytochrome bo and VHb was suggested by Tsai et al (3).…”
Section: Construction Of Peg202::vgb and Pjg4-5::cyo Bo Ubiquinolsupporting
confidence: 75%
“…Using immunogold labeling of VHb in E. coli and Vitreoscilla, the cellular localization of VHb has been recently determined to be in the cytoplasm, concentrated in the outer perimeter near the cell membrane (13). The same study showed that VHb bound to bacterial (E. coli and Vitreoscilla) respiratory membranes, which would account for its localization.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…An inspection of the absorption spectrum of the unliganded derivative is consistent with the presence of a pentacoordinated heme adduct. It is worth noting that despite the contribution attributed to the flavin absorption (shoulders at 470 and 490 nm with a broad tail toward the visible region), the peak at 645 nm and the broad Soret band characterized by a low molar absorptivity and centered at ϳ403 nm are clearly identified as typical pentacoordinate high spin marker bands in which the proximal histidine is the fifth ligand (22). The spectrum of the fully liganded species is typical of hexacoordinate low spin adducts observed in all other hemoglobins and myoglobins.…”
Section: Fhp) and Thrmentioning
confidence: 99%
“…The VHb gene is a hemoglobin-like gene present in the chromosome of the aerobic Gram-negative bacterium, Vitreoscilla sp., whose protein plays an important role in oxygen transfer [11,17,22,25]. Heterologous expressions of the VHb gene in several microorganisms, including E. coli, stimulates ATP generation by promoting efficient oxygen transfer in an oxygen-limited environment, leading to enhanced cell growth and protein synthesis [2,5,14,15,27]. A VHb gene cloned in a fungal expression vector, pBARGPE1, containing a selection marker of an Ignite/basta-resistance (bar) gene [12] was kindly provided by Prof. G. T. Chun of Kangwon University, Korea.…”
mentioning
confidence: 99%